Strategi Kompetensi Manajerial Kepala Sekolah Dalam Mewujudkan Sekolah Ramah Anak di Sekolah Dasar - Haryanti, Sri; Narimo, Sabar; Fuadi, Djalal; Minsih, Minsih (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the managerial competence strategies of school principals in realizing child-friendly schools at SD Muhammadiyah Program Unggulan Jatipuro. The focus of this research is to explore how the principal utilizes managerial competence to create a safe, comfortable environment that supports the holistic development of children. The research method used is a qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation. The data obtained were analyzed using thematic analysis. The results of the study show that the principal has implemented effective managerial strategies in creating a child-friendly school. Some of the efforts made include ongoing teacher training, improvement in the management of school facilities, and the implementation of an anti-bullying policy. However, there are challenges faced, such as the limited number of teachers with special skills to handle children with special needs, limited facilities, and a constrained budget. The principal also faces challenges in consistently implementing the policies on the ground. The conclusion of this study is that, despite some challenges, the implementation of the principal’s managerial strategies has had a positive impact on creating a child-friendly school. The solutions proposed by the principal, such as strengthening teacher training, enhancing cooperation with external parties, and conducting more intensive program evaluations, are expected to strengthen the implementation of the child-friendly school program. This study contributes to the development of more inclusive educational policies that support the optimal growth and development of children.